Simultaneous determinations of τ polarisation and vτ, helicity using the decay τ → a1vτ - Dova, María Teresa (1997)
A method is presented to extract tau polarisation Pτ and tau neutrino helicity γVA simultaneously using τ leptons produced at the Z⁰ which decay into a1 and vτ. It provides better sensitivity than independent fits to Pτ or γVA separately and in fact can be shown to be optimal. Estimates of sensitivity from Monte Carlo studies and comments regarding the use of the technique in experiments are also presented. We also discuss how results of tau polarisation determinations using other decay modes may be included.